From “stars” to nano: porous poly(ethylene glycol) hydrogel films and nanosheets as a versatile platform for sensing and nanofabrication - Zharnikov, Michael (Nano research, 2024)
The use of bioinert materials is crucially important for medicine and bioengineering. The most popular systems in this context are oligo- and poly(ethylene glycols) (OEGs and PEGs), applied generally in different forms as bulk materials, thin films, and functional molecular groups. Here, I review the fabrication, properties, and applications of porous hydrogel PEG films (PHFs) and nanosheets (PHNs) formed by thermally activated crosslinking of amino- and epoxy-terminated, star-branched PEG oligomers with variable molecular weight. These systems possess various useful characteristics, including tunable thickness and porosity, hydrogel properties, bioinertness, robustness, and extreme elasticity. They can serve as the basis for composite materials, advanced nanofabrication, and lithography, bioinert supports for high-resolution transmission electron microscopy, susceptible elements in micro-electromechanical systems, and basic building blocks of temperature, humidity, chemical, and biological sensors. Representative examples of the respective applications are provided. Even though these examples span a broad field-from nanoengineering to biosensing, the applications of the PHFs and PHNs are certainly not limited to these cases but can be specifically adapted and extended to other fields, such as tissue engineering and drug delivery, relying on versatility and tunability of these systems.
Veröffentlicht: 1. August 2024
Gesehen am 17.03.2025